Kurdish EFL University Students’ Difficulties in Using English Determiners - Mustafa, Sumaya Khalid; Hassan, Ikhlas Mahdi; Ghafor, Omar Fouad; Ahmad, Hedayat Muhammad; Fathulla, Paywand HamaRauf; Saed, Shaema Abdulla; Nabard, Pasand (Journal of Linguistics and Social Sciences, 2023)
Determiners are morphemes that occur before a noun to express what the noun refers to and are used to identify things. The present study attempts to find the difficulties Kurdish EFL students face when using English determiners. The study also tries to evaluate Kurdish EFL students' ability to use English determiners appropriately at recognition and production levels. To achieve the study's aims, answer its questions, and test the hypotheses, the researchers constructed an achievement test to collect data and measure the students' performance with regard to English determiners at both recognition and production levels. The test was answered by thirty-one English department students at Halabja university who were chosen randomly including both genders. The data collected from the test were analyzed, and the results showed that the participant's performance at the production level was lower than the recognition level. The results necessitate more training on using English determiners through comprehensive lessons and activities that can enhance Kurdish EFL learners' language proficiency